Dietary Changes During COVID-19 Lockdown in Adults With Type 1 Diabetes on a Hybrid Artificial Pancreas - Vetrani, Claudia; Calabrese, Ilaria; Di Rienzo, Silvia; Pagliuca, Mariasofia; Rivieccio, Annamaria; De Angelis, Raffaele; Riccardi, Gabriele; Rivellese, Angela Albarosa; Annuzzi, Giovanni; Bozzetto, Lutgarda (Frontiers in Public Health, 2021)
In this retrospective analysis, we examine the impact of the lockdown of the coronavirus pandemic (COVID-19) on eating habits in individuals with type 1 diabetes (T1D) on a hybrid artificial pancreas (HAP). Dietary composition before and during lockdown was assessed by 7-day food records of 12 participants with T1D on HAP (three men and nine women, ages 38 ± 13 years, HbA1c 6.8 ± 0.3%, M ± SD). Continuous glucose monitoring (CGM) metrics and lifestyle changes (online questionnaire) were also assessed. Compared to prelockdown, reported body weight tended to increase during lockdown with no changes in total energy intake. Participants significantly decreased animal protein intake (−2.1 ± 3.7% of total energy intake, p = 0.048), but tended to increase carbohydrate intake (+17 ± 28 g/day, p = 0.052). These changes were induced by modifications of eating habits at breakfast and lunch during weekdays. Patients consumed more cereals (+21 ± 33 g/day, p = 0.038), whole grain (+22 ± 32 g/day, p = 0.044), and sweets (+13 ± 17 g/day, p = 0.021), and less animal protein sources (−42 ± 67 g/day, p = 0.054). Participants showed a more regular meal timing and decreased physical activity. Blood glucose control remained optimal (time-in-range 76 ± 8 vs. 75 ± 7% before lockdown), and daily total insulin infusion increased (42 ± 10 vs. 39 ± 12 I.U., p = 0.045). During the lockdown, patients with T1D on HAP modified dietary habits by decreasing animal protein and increasing carbohydrate intake. This increase, mainly concerning whole grain and low-glycemic-index products, did not influence blood glucose control.